(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article the political analysis of public and state activities as well as political views Zhaһanshy Dosmukhamedov based on historical sources and works of local researchers. Heritage Zhaһanshy Dosmukhamedov as chairman of Western Alashorda still not widely appreciated, his case nedostotachno studied from the point of view of political science. Zhaһansha Dosmukhamedov being a lawyer, a social worker, a public official, teacher, jurist, son of his people deeply understand the responsibility before the people really realize their aspirations, fought for national interests and the creation of the state of the Kazakhs. The article discusses his work, the idea of preserving the national identity, the future structure of the state, the importance of creating an autonomous democratic republic within the federation. Key words: Zhaһansha Dosmukhamedov, state, national interest, Alash Orda, Alash, federation, autonomy, democratic republic, the fate of the nation.